2012
DOI: 10.1186/1471-2334-12-40
|View full text |Cite
|
Sign up to set email alerts
|

Non-capsulated and capsulated Haemophilus influenzaein children with acute otitis media in Venezuela: a prospective epidemiological study

Abstract: BackgroundNon-typeable Haemophilus influenzae (NTHi) and Streptococcus pneumoniae are major causes of bacterial acute otitis media (AOM). Data regarding AOM are limited in Latin America. This is the first active surveillance in a private setting in Venezuela to characterize the bacterial etiology of AOM in children < 5 years of age.MethodsBetween December 2008 and December 2009, 91 AOM episodes (including sporadic, recurrent and treatment failures) were studied in 87 children enrolled into a medical center in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
2
8
2
Order By: Relevance
“…The resistance of S. pneumoniae serotype 19A to penicillin was mainly intermediate, thereby highlighting the lack of resistance from this usually penicillin-resistant serotype. 39 These findings are consistent with recent reports from other countries, 23 , 24 and underscore the observed change in antibiotic resistance to penicillin over the past decade, particularly because a high percentage of samples were resistant to penicillin in the previous South African study. 28 Similarly, most other vaccine serotypes were also intermediate in their resistant to penicillin.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The resistance of S. pneumoniae serotype 19A to penicillin was mainly intermediate, thereby highlighting the lack of resistance from this usually penicillin-resistant serotype. 39 These findings are consistent with recent reports from other countries, 23 , 24 and underscore the observed change in antibiotic resistance to penicillin over the past decade, particularly because a high percentage of samples were resistant to penicillin in the previous South African study. 28 Similarly, most other vaccine serotypes were also intermediate in their resistant to penicillin.…”
Section: Discussionsupporting
confidence: 89%
“…Our study also indicated that NTHi-positive episodes were resistant to trimethoprim/sulfamethoxazole (60.8%) and ampicillin (13.9%), consistent with previous reports from South Africa. 24 , 28 Furthermore, the low resistance for S. pneumoniae and NTHi to amoxicillin/clavulanate supports its continued use in the treatment of AOM as recommended in South Africa. 37 In addition to antibiotic treatment for AOM, vaccination indicated against AOM may help control the associated disease burden.…”
Section: Discussionmentioning
confidence: 97%
“…Non-typeable Haemophilus influenzae (NTHi) often causes upper respiratory tract infections and although rare, carries a potential risk of invasive disease especially in at-risk populations such as the elderly, children and neonates [1,2]. Since the introduction of H. Influenzae vaccine, there has been a dramatic decline in mortality and morbidity associated with invasive disease caused by serotype b [3].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in the past assessed the etiology and serotype distribution of bacterial pathogens causing AOM in various countries [ 27 30 ] including Latin American countries such as Chile, [ 31 ] Colombia, [ 32 ] Mexico, [ 33 ] and Venezuela. [ 34 ] However, recent epidemiological data in terms of AOM disease burden in Chile are limited.…”
Section: Introductionmentioning
confidence: 99%